MICROBIOLOGICAL ASSESSMENT OF WATER CONSUMED BY A RURAL POPULATION OF ILHA SOLTEIRA – SÃO PAULO - Fialho, J. M.; Leite, M. A.; Pião, A. C. S.; Dornfeld, C. B.; Alves Prado, H. F. (Revista Brasileira de Engenharia de Biossistemas, 2017)
The quality of water in rural areas is difficult knowledge, since the distribution does not occur equally in all places, which implies the difficulty of individual analyzes. Thus, the water for human consumption of in eighteen rural lots in the Ilha Solteira was assessed in relation to some physical and chemical parameters and, in particular, to the Total coliforms and Thermotolerant (Escherichia coli E. c) between January and September 2015, being this water from the municipal water supplies or wells. The parameters were compared with those established as acceptable by means of Decree nº 2.914/2011 of Ministry of Health, which establishes the standards of potability of water for human consumption. The values of total coliforms ranged from 3 to 240 MPN/100 mL and were detected in all lots. The thermotolerant coliforms were found in 39% of water samples from the lots and the results ranged from 3 to 23 NPM/100 mL while the enteroinvasive E. c (EIEC) bacterium was also confirmed in the same plots. The turbidity ranged from 0 to 16.0 UT; pH between 5.1 to 8.6 and electrical conductivity (E.C.) between 19.7 to 303.0 μS cm-1. The results presented here, it was found that 100% of water intended for human consumption in the rural area of Ilha Solteira does not meet the standards of potability.